Keene on the market : trade to win using unusual options activity, volatility, and earnings - Keene, Andrew, 1979- (Wiley trading series, 2013)
A leading expert unveils his unique methodology for options trading Options provide a high leverage approach to trading that can significantly limit the overall risk of a trade or provide additional income. Yet, many people fail to capitalize on this potentially lucrative opportunity because they mistakenly believe that options are risky. Now options expert Andrew Keene helps aspiring investors to enter this sector by explaining the principles of the options market and showing readers how to utilize calls and puts successfully. Leading options expert Andrew Keene demystifie.